Dietary non-adherence and circadian rhythm in diabetic patients: A case report - Nur Indahsari, Lily; Chayati, Nur (Palembang MediRose Publisher, 2024)
Background: Non-compliance with both medical and non-medical therapy regimens, such as dietary management, can lead to elevated blood glucose levels in patients with diabetes mellitus. Additionally, disturbances in circadian rhythms can impact glucose metabolism. The combination of these factors requires further investigation to understand their role in increasing glucose levels. Understanding how dietary non-adherence and circadian rhythm disturbances affect glucose metabolism may help improve glycemic control. Objective: This study aims to assess dietary non-adherence and circadian rhythm disturbances in a patient with type 2 diabetes mellitus and uncontrolled blood sugar. Case: A 65-year-old male patient was admitted to the inpatient unit from the emergency department. He had been diagnosed with type 2 diabetes mellitus since 2002. Blood sugar monitoring was performed every 12 hours using a sliding scale. Despite receiving a hospital-prescribed diet, the patient consumed additional foods such as bread, donuts, biscuits, and milk from outside sources. The patient also exhibited an irregular sleep pattern, sleeping only about 5 hours per night, going to bed after 9 p.m., waking up frequently during the night, and eating snacks (e.g., small bread) before sleep. On the first day, the morning glucose level (GDS) was 313 mg/dL and 140 mg/dL in the evening. On the second day, the morning GDS was 228 mg/dL, and 138 mg/dL in the evening. On the third day, the morning GDS was 145 mg/dL. The patient was discharged in the afternoon with an increased insulin dose from 6 to 8 units. Conclusion: Dietary non-adherence and circadian rhythm disturbances are potential risk factors for elevated blood glucose levels in patients with type 2 diabetes mellitus. Providing health education, continuous monitoring, and support to both the patient and family can encourage adherence to medical regimens and improve health outcomes.